MANFAAT SOSIAL MEDIA DALAM E-GOVERNMENT DI INDONESIA - Ainaya Nazilatul Fathinia Muqoffa; Mawar, Mawar; Novinda Serikandi (Badan Penerbit STIEPARI Press, 2022)
Social media is one of the options used by the government to communicate with the people and carry out its function in providing public services. Government social media management requires an organizational culture with support from all levels of government officials to be able to share information with the public. Utilization of e-government which is intended to make management and government work more effective and efficient. In addition, with the existence of e-government in e-governance, the relationship between the Government, business actors, private sector and the public can be more responsive, effective, efficient, transparent and accountable. The use of social media for e-Government also has an impact or risk that needs to be taken into account. So that the expected results can be achieved, then in using social media the government needs a strategy in the use of social media.